Effect of renal artery stenting on renal function in patients with ischemic nephropathy - Ilkay, E; Günal, AI; Yavuzkir, M; Dagli, N; Karaca, I; Celiker, H; Arslan, N (Int Heart Journal Assoc, 2004)
The aim of this study was to evaluate the effects of stenting on blood pressure and renal functions in azotemic patients with proximal/ostial atherosclerotic renal artery stenosis. Thirteen azotemic patients (5 females, 8 males, average age, 62.7 +/- 8.3 years) who had renal artery stenosis were included in the Study. Their blood pressure, estimated glomerular filtration rate (EGFR), and creatinine levels were measured at baseline and during follow-up. Stents were implanted successfully in all of the cases. The average stent diameter and stent length were 7.2 +/- 0.5 mm and 17.2 +/- 3.4 mm, respectively. Antihypertensive drug was abandoned in 1 (7.6%) patient, reduced in 10 patients (76.9%), and not changed ill 2 (15.3%) patients. Significant improvement was observed in the mean serum creatinine level at the 12(th) month when compared with baseline (2.56 +/- 0.88: 1.83 +/- 0.62, P<0.001). EGFR was 18.38 +/- 4.64 before the procedure and 22.67 +/- 3.81 during follow-up (P<0.0001). According to the EGFR criteria, renal function was determined to be worse in 1 (7.6%) patient, stabilized in 2 (15.3%), and improved in 10 (76.9%) patients. One patient died during the follow-up period. Angiographic restenosis was observed in 2 (15.3%) patients. Follow-up major events were observed in 3 (23%) patients. Stenting azotemic patients with renal artery stenosis is a reliable and effective procedure for achieving an improvement in renal function.
Keywords: renal artery stenosis; Azotemia; hypertension; stent